Theme Session H – Future Integrated Ecosystem Assessment ... - ICES (ASC 2023 - Theme session H, 2024)
Book of abstracts of theme session H: Future Integrated Ecosystem AssessmentsConveners: Benjamin Planque (Norway), Paulina Ramírez-Monsalve (Norway), Carolyn Faithfull (Sweden)​CM 32: Future steps to move fisheries management towards an ecosystem-based approachCM 75: Using food web indicators to assess the impact of fisheries on marine ecosystemsCM 102: Effects of seasonality on the structure and functioning of a Mediterranean Sea ecosystemCM 130: Integrated Assessment of the Canary Current large marine ecosystem with a focus on the Canary Islands and Senegal-Gambia-Guinea-Bissau subregionsCM 131: How and why do marine ecosystem indicators change with scale and what does it meanCM 176: A systematic review of Management Strategy Evaluations in fisheries: In search of future challenges in a context of global changeCM 177: Strategic Environmental Assessment (SEA) for seas: towards a more strategic and environmentally-oriented marine spatial planning processesCM 299: ICES IEA groups: what they are doing, why, ...